Advancing A Confused Subfield: A Review of Crenshaw and LaFree's Countering Terrorism. Issue 1 (2nd January 2019) - Hultquist, Philip
Abstract : The subfield of terrorism studies remains confused about its principal concept. Few agree on what the term means, which creates obvious problems for operationalization. Crenshaw and LaFree (2016) address this issue directly and find a way to advance the subfield by offering unique analytical insights. They further our knowledge of the rarity of terrorist plots as well as the method for how most are thwarted. Moreover, they provide a fruitful critique of government overclassification of data that makes the production of sound policy-relevant research difficult, which has the perverse effect of making counterterrorism less effective. Nonetheless, the book suffers from conceptual confusion about the tactic of terrorism when it limits its primary scope to a subset of groups that use the tactic frequently, but not exclusively—that is, those Salafi groups that use an extremist interpretation of the term jihad . The book should be read widely, by researchers and practitioners, to learn from its insights, but also critically in the hope that future work can advance this subfield to examine terrorism for the full range of ideological groups who use the tactic.